Association between KCNE1 G38S gene polymorphism and risk of atrial fibrillation: A PRISMA-compliant meta-analysis. Issue 25 (June 2017) - Jiang, Yu-Feng; Chen, Min; Zhang, Nan-Nan; Yang, Hua-Jia; Xu, Lang-Biao; Rui, Qing; Sun, Si-Jia; Yao, Jia-Lu; Zhou, Ya-Feng
Abstract: Background: Previous case-control studies on association between KCNE1 G38S polymorphism and risk of atrial fibrillation (AF) have been published but because of the conflicting results and small sample size of individual studies, the consolidated result is still controversial. Objectives: The aim of this study was to explore the relationship between KCNE1 G38S polymorphism and risk of AF. Methods: We performed a comprehensive literature search on PubMed, Embase, OVID, Web of Science, Wan Fang, and CNKI databases up to March 10, 2017 in English and Chinese languages. Two of the authors individually extracted study data and assessed the study quality using Newcastle-Ottawa scale. Odds ratios (ORs) and 95% confidence intervals (CIs) were combined in different genetic models for evaluation using a random-effect model or fixed-effect model according to interstudy heterogeneity. Results: There were totally 14 independent case-control studies of 2810 patients and 3080 healthy controls included. Significant associations were found between KCNE1 G38S polymorphism and AF in overall population under all genetic models: allelic (OR: 1.34, 95% CI: 1.24–1.45, P  < .001), homozygous (OR: 1.90, 95% CI: 1.61–2.24, P  < .001), heterozygous (OR: 1.43, 95% CI: 1.21–1.68, P  < .001), recessive (OR: 1.42, 95% CI: 1.20–1.69, P  < .001), dominant genetic model (OR: 1.62, 95% CI: 1.39–1.89, P  < .001). Subgroup analyses indicated similar association in Chinese and white. Conclusions: The G38S polymorphism in the KCNE1 gene can significantly increase the risk of AF in both Chinese and white. Abstract : Supplemental Digital Content is available in the text